Exploring Teaching Evaluation Research Trends: A Scopus-Based Bibliometric Study - Mufidah, Afifah Lutfi; Azani, Mohammad Zakki; Apriantoro, Muhamad Subhi (Universitas Muhammadiyah Surakarta, 2023)
This study aims to map the development and direction of Exploring Teaching Evaluation research in Scopus-indexed publications. Bibliometric analysis techniques were used in this study to explore all publications indexed in the Scopus database on Exploring Teaching Evaluation from 1972, the first year of research on the theme, until 2023. The data obtained was analysed using Excel and R/R-Studio. VOSviewer was used to analyse the simultaneous occurrence of keywords and document citations visually. The author found 1,56 publications that matched the criteria, function, and subject. The results of this study show an annual growth rate of 8.17% with the most publications on Exploring Teaching Evaluation in 2022. The United States led the publication with 396 documents from Monash University. Galarce-Miranda, c and Gormaz-Lobos, D. led the way with the number of publications as many as 4 documents with the theme Exploring Teaching Evaluation. Researchers conducted bibliometric analysis limited to Scopus data. Other national and international databases should have been considered in this study. The study is completed by presenting a brief overview of the literature accessible to researchers working in the field of education and providing recommendations for future research.